In vivo knee rotational stability 2 years after the ACL reconstruction using a quadriceps tendon graft with bone block and bone-patellar tendon-bone graft - Komzák, Martin; Hart, Radek; Náhlík, David; Vysoký, Robert (Archives of orthopaedic and trauma surgery, 2022)
INTRODUCTION: The aim of this prospective randomised study was to evaluate clinical results and rotational stability at least 2 years after single-bundle anatomic anterior cruciate ligament reconstruction using a quadriceps tendon graft with bone block (BT) and bone-patellar tendon-bone graft (BTB). MATERIALS AND METHODS: In both groups (BT and BTB), 40 patients selected prospectively at random were evaluated. The mean follow-up after the surgery was 28 months (range 24-33 months). A navigation system was used to measure rotational stability of the knee joint. Cincinnati, Lysholm, and IKDC scores and visual analog score (VAS) were used to evaluate clinical results and the non-parametric Wilcoxon test was used for the statistical analysis. RESULTS: After the BT reconstruction, the mean internal rotation of the tibia (IR) was 9.5°. In the contralateral healthy knee joint, IR was 8.6° at average. After the BTB reconstruction, the mean IR was 9.9°. In the contralateral healthy knee joint, IR was 8.7° at average. We did not find any statistically significant difference in IR stability between BT and BTB reconstruction. In terms of clinical results, regarding the VAS, patients perceive significantly more pain after the BTB reconstruction (p < 0.05). Kneeling was reported more difficult and painful after BTB reconstruction. CONCLUSIONS: The BT reconstruction of the ACL provides similar clinical results, less pain, better flexion and the same rotational stability of the knee in comparison with the BTB reconstruction.
Keywords: nestabilita kloubu; Knee Joint; Tendons; poranění předního zkříženého vazu; lidé; Rotational stability; rekonstrukce předního zkříženého vazu; šlachy; štěp kost-čéškový vaz-kost; ACL; Quadriceps tendon graft; Anterior Cruciate Ligament Reconstruction; bolest; štěp z vazu čéšky; prospektivní studie; Anterior Cruciate Ligament Injuries; Prospective Studies; Bone-Patellar Tendon-Bone Grafts; Pain; Joint Instability; kolenní kloub; Bone-Patellar Tendon-Bone Grafting; Humans